PEMAHAMAN KONSEPTUAL SISWA DIKAJI DARI GAYA KOGNITIF DALAM MATERI PERTIDAKSAMAAN LINEAR SATU VARIABEL DI SMP - Setiawati, Dwi; Sugiatno, Sugiatno; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background in this research is conceptual understanding is one of the abilities students must have to be able to succeed in learning mathematics. Conceptual understanding is students mastery of mathematical concepts, operations, and relations. In conceptual understanding influenced by the cognitive style students have. Because each student has a unique way of learning related to how information is received and processed, attitudes toward information, and habits related to the learning environment. The purpose of this research is to describe the conceptual understanding of students assessed from cognitive style in the material linear inequality of one variable in SMP Negeri 1 Sungai Raya. The research method used is descriptive method in the form of case study. Data collected using tests and interviews. The subjects of this research were students of grade VII A consisting of field independent cognitive style students and field dependent cognitive style student. The results of this research are students conceptual understanding of field independent cognitive style able to fulfill four indicators of conceptual understanding. Whereas students conceptual understanding of field dependent cognitive style is able to fulfill two indicators of conceptual understanding.Â Keywords: Cognitive Style, Conceptual Understanding, Linear inequality one variable